MASA DEPAN PESANTREN PASCA UU 20/2003 TENTANG SISTEM PENDIDIKAN NASIONAL DAN PP 55/2007 TENTANG PENDIDIKAN AGAMA DANPENDIDIKAN KEAGAMAAN - Suparta, Suparta (Analisis: Jurnal Studi Keislaman, 2014)
THE FUTURE OF THE PESANTREN (BOARDING SCHOOLS) FOLLOWINGTHEENACTMENTOFNATIONALEDUCATION ACT   NO.   20/2003  AND   GOVERNMENT    REGULATION NO. 55/2007  ON RELIGIOUS EDUCATION.  The reformation movement   in   Indonesia,   including  in   education   sphere,   is reinforced   by  the   principles   of  democracy,  decentralization, justice,  and  human  rights.  In  the  national  education system, the  reform  is done  to  eliminate  discrimination, both  in public and private  educational  institutions,   as well as to  abolish  the dichotomy between religious education and general education. As the consequences of the enactment of National Education Act No. 20 / 2003, the elimination of discrimination  becomes a necessity. Given that one of the principles of educational democracy requires the involvement of all elements in policy making, the pesantren, as one element  of National Education  System,  is entitled  to be involved. This involvement will not only to absorb the aspirations of the boarding school, but also to encourage the growth of cooperation between the government and the pesantrencircles  in realizing the more qualified and dignified education.